ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI MINAT SANTRI MELANJUTKAN STUDI DI UNIVERSITAS IBRAHIMY: PENDEKATAN MIXED MTHOD - Wahedi, Su'ud; Asmito, Asmito (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2024)
The disparity in the number of students at each university is not always evenly distributed. The difference is quite large. It is recorded that some universities can accept tens of thousands of students per year. In addition, there are also universities that only accept hundreds of students per year. Many factors cause this high disparity. This research tries to examine the factors that influence students’ interest in continuing their studies at Universitas Ibrahimy Sukorejo Situbondo. The research method applied was a mixed method with a sample of 236 final year students from schools under the auspices of Salafiyah Syafi’iyah Sukorejo Situbondo Islamic Boarding School. The results show that higher education accreditation status and parental support have a significant positive effect on students’ interest in continuing their studies at Universitas Ibrahimy. In addition, facilities and infrastructure influence students’ interest in continuing studies but have a negative coefficient. Another dimension, namely the amount of education costs, has no effect on students’ interest in continuing studies. The researcher recommends to future researchers to increase the number of samples and dimension, such as geographic distance, opportunities for acceptance and cost of living as well as other dimensions that are considered to be related to students’ interest in continuing studies so that the research results obtained are more comprehensive.